2019
DOI: 10.3389/fmars.2019.00288
|View full text |Cite
|
Sign up to set email alerts
|

A Change of Mind: Applying Social and Behavioral Research Methods to the Assessment of the Effectiveness of Ocean Literacy Initiatives

Abstract: Assessment of environmental literacy and ocean literacy focus on increasing knowledge and awareness. The goal of ocean literacy initiatives is ultimately to enable behavior change (whereby citizens take direct and sustainable action) to achieve sustainable solutions to marine environment issues. The application of social and behavioral research methods provides powerful tools for assessing if ocean literacy initiatives are effective at increasing participant's knowledge and awareness of an issue, its causes an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 34 publications
1
28
0
Order By: Relevance
“…Building ocean literacy amongst communities or groups of individuals is an approach to encourage responsible public behaviour towards the ocean and its resources (Fielding et al 2019 ). The ‘goal’ of ocean literacy initiatives is to enable behaviour change, whereby citizens engage in sustainable actions to achieve solutions to marine issues (Ashley et al 2019 ). In contrast, a lack of ocean literacy presents a significant obstacle to engaging society in environmentally sustainable behaviours (McCauley et al 2019 ).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Building ocean literacy amongst communities or groups of individuals is an approach to encourage responsible public behaviour towards the ocean and its resources (Fielding et al 2019 ). The ‘goal’ of ocean literacy initiatives is to enable behaviour change, whereby citizens engage in sustainable actions to achieve solutions to marine issues (Ashley et al 2019 ). In contrast, a lack of ocean literacy presents a significant obstacle to engaging society in environmentally sustainable behaviours (McCauley et al 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…small and large scale, experiential learning, multiple age-groups, technological/digital, etc.). When ocean literacy initiatives are tailored to relevant issues and communities, they increase knowledge uptake and engender attitudes of concern that can promote personal action (Ashley et al 2019 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have shown that the inclusion of citizen science in the monitoring of IAS (e.g., using smartphone apps, online platforms) can significantly improve the database and also the knowledge of the overall IAS abundance and spread (Freiwald et al, 2018;César de Sá et al, 2019;Giovos et al, 2019). Ocean literacy initiatives have been shown to be effective and to have positive effects on behavior changes of citizens, who then take direct and sustainable actions toward sustainable solutions for marine environments (Ashley et al, 2019).…”
Section: Recognizementioning
confidence: 99%